Prenatal air pollutant exposure and occurrence of atopic dermatitis. (24th September 2015) - Huang, C.C.; Wen, H.J.; Chen, P.C.; Chiang, T.L.; Lin, S.J.; Guo, Y.L.
Summary: Background: Hereditary and environmental factors have been related to the occurrence of atopic dermatitis (AD) in early childhood. However, the role of prenatal and early postnatal exposure to air pollutants has not been totally elucidated. Objectives: To evaluate the association between prenatal air pollutant exposure and occurrence of AD. Methods: In total 24 200 infant–mother pairs were recruited to participate in the Taiwan Birth Cohort Study in 2005 using multistage stratified sampling. Medical history, including physician‐diagnosed AD, was inquired by questionnaire at the infant's age of 6 months. Monthly averages of five criteria air pollutants – NO2, CO, O3, SO2 and PM10 – were retrieved from 66 air‐quality‐monitoring stations, and interpolated to all administrative districts using the kriging method. Exposure data during each of the three gestational trimesters and three months after birth were calculated for each study subject, and odds ratios (ORs) of AD occurrence were calculated by logistic regression. Results: Among the participants, 16 686 mother–infant pairs were qualified for and included in the analysis. Among them, 1206 infants (7·2%) had been diagnosed as having AD before the age of 6 months, and the prevalence was higher in boys (8·3%) than in girls (6·1%). The occurrence of AD was significantly associated with CO exposure during the whole gestational period [adjusted OR (aOR) 1·37, 95% confidence interval (CI) 1·06–1·78] and the first trimester (aOR 1·51, 95% CI 1·16–1·97). We did not observe any significant association among the other air pollutants during either the whole gestational period or any period of the three trimesters and 3 months after birth. Conclusions: Our study found a relationship between AD occurrence and gestational exposure to CO, where exposure during the first trimester seemed to be the most important. Abstract : What's already known about this topic? The role of prenatal exposure to air pollution in the development of atopic dermatitis is lacking from previous studies. What does this study add? Prenatal exposure to carbon monoxide was related to atopic dermatitis. Exposure during the first trimester seemed to be the most relevant.